2013
DOI: 10.1007/s00534-013-0615-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted pancreatic surgery

Abstract: Background Pancreatic surgery is a challenging application of minimally invasive surgery. Due to the complexity of the surgical technique, requiring dissection along major abdominal vessels as well as delicate reconstruction involving biliary, pancreatic and enteric anastomoses, reports on laparoscopic pancreatic surgery have been scanty. With the advent of robotic-assisted surgery, however, the increased dexterity granted by endo-wristed instruments, the improved three-dimensional vision and the computer filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
(65 reference statements)
0
11
0
2
Order By: Relevance
“…It is debatable whether the superior approach for PD is totally robotic surgery or laparoscopic/robotic hybrid surgery. Fernandes et al reported that a totally robotic approach was superior, whereas other studies reported that a hybrid laparoscopic and robotic approach consisting of laparoscopic dissection and robotic reconstruction was superior . The present study used a hybrid approach; laparoscopic surgery enabled a prompt response and wide range of motion during the dissection phase, while robotic surgery enabled fixed and fine movement during the anastomosis phase.…”
Section: Discussionmentioning
confidence: 76%
“…It is debatable whether the superior approach for PD is totally robotic surgery or laparoscopic/robotic hybrid surgery. Fernandes et al reported that a totally robotic approach was superior, whereas other studies reported that a hybrid laparoscopic and robotic approach consisting of laparoscopic dissection and robotic reconstruction was superior . The present study used a hybrid approach; laparoscopic surgery enabled a prompt response and wide range of motion during the dissection phase, while robotic surgery enabled fixed and fine movement during the anastomosis phase.…”
Section: Discussionmentioning
confidence: 76%
“…3 These findings were not confirmed in a meta-analysis of 9 nonrandomized studies comparing open and minimally invasive (both laparoscopic and robotic) PD, where the time disparity in favor of open PD was attributed to the laparoscopic approach. 20 In our series, the operative time of robot-assisted PD did not decrease with increasing experience, probably due to a contemporary increase in the complexity of the cases and a reduction in the conversion rate.…”
Section: Discussionmentioning
confidence: 51%
“…Verschiedene Gruppen haben in den letzten Jahren Ergebnisse zur roboterassistierten Pankreaschirurgie veröffentlicht. Die bisher größte Fallserie umfasst 134 Patienten (60 Pankreatikoduodenektomien, 46 Pankreaslinksresektionen sowie 3 zentrale Resektionen und eine totale Pankreatektomie) [37,38]. In einer vergleichenden Analyse war die roboterassistierte Pankreaslinksresektion mit einer deutlich längeren Operationsdauer und erheblich höheren Kosten als bei der konventionellen laparoskopischen Pankreaslinksresektion verbunden [39].…”
Section: Roboterassistierte Pankreaschirurgieunclassified
“…Auch die roboterassistierten Pankreatikoduodenektomien scheinen mit ähnlichen Ergebnissen einherzugehen wie die laparoskopischen Pankreatikoduodenektomien - bei deutlich höheren Kosten und einer längeren Operationsdauer [8]. Die grundsätzliche Machbarkeit konnte jedoch in verschiedenen Serien gezeigt werden [37,41,42]. Eine kürzlich veröffentlichte Metaanalyse bestätigte die Machbarkeit der roboterassistierten Pankreaschirurgie ohne Nachteile bezüglich der perioperativen oder onkologischen Qualität [43].…”
Section: Roboterassistierte Pankreaschirurgieunclassified